MENGURAI TANTANGAN MANAJEMEN MUTU PENDIDIKAN MADRASAH: TINJAUAN DARI INPUT-PROSES-OUTPUT - Efendi, Mardian; Asha, Lukman; Wanto, Deri (Educational Leadership: Jurnal Manajemen Pendidikan, 2024)
Achieving quality and quality in educational institutions can be realized through the implementation of effective management. In the implementation of this management, educational institutions are often faced with various problems related to the quality and quality of input-process-output. This research was conducted by focusing on analyzing the problems that arise in educational institutions, especially madrasah, related to quality and quality. Understanding the existing problems provides valuable insights and experiences to improve quality management and quality in madrasah in the future. The research method used is a qualitative research method with a library research approach. This research indicates that the challenges in quality management and quality of madrasah include: low standards of educator qualifications, performance of educators who have not reached their maximum potential, damage to infrastructure and facilities, shortage of educators, availability and quality of learning resources that are not optimal, restrictions on financial resources, supervisory performance that is not optimal, and lack of competence in structural management.